Comparison of kinematics in repeated 30 m sprints in female soccer players - van den Tillaar, R. (ISBS Proceedings Archive (Michigan), 2017)
The aim of this study was to examine the effect of sprint repetition on running kinematics (step length, frequency, contact and flight time and vertical stiffness) during a repeated sprint ability test in female soccer players. Seventeen subjects performed seven 30m sprints every 30th second in one session. Kinematics was measured with an infrared contact mat and laser gun and running times with an electronic timing device. The main findings were that sprint times increased in the repeated sprint ability (RSA) test. Furthermore, the main changes in kinematics during the RSA test were an increased contact time and decreased step frequency and vertical stiffness, while no change in step length was observed. Employing this approach in combination with laser gun and infrared mat over 30 m makes it very easy to analyse kinematics in repeated sprint ability in training. It was concluded that fatigue induced in repeated 30 m sprints in female soccer players resulted decreased step frequency and increased contact time and decrease vertical stiffness.